Olonets-Karelian-to-X XML Dictionary - Rantakaulio, Timo; Rueter, Jack (Zenodo, 2022)
This .zip file includes XML dictionary document, divided according to part of speech, for Olonets-Karelian (LIvvi, ISO-693: olo) to Finnish and Russian. The Livvi-Finnish glosses originate from the Kone Foundation's "Language Programme" and represent work done by Timo Rantakaulio (Creation of morphological parsers for minority Finno-Ugric languages [Morfologisten jäsentimien luominen suomalais-ugrilaisille vähemmistökielille] 2013–2014) in close collaboration with Jack Rueter, who was able to formulate the finite-state morphological description of the Olonets-Karelian language on the basis of Timo's expertise. Subsequently, the Olonets-Karelian and Russian language pair has also been aligned in tandum with the Livvi-Finnish pair, but there may be some descrepencies, as no two languages follow identical lexical systems, much less three. The XMLs contain both lemma and stem forms of Livvi with an indication of distinct paradigm information. : {"references": ["Rueter, Jack (2014): The Livonian-Estonian-Latvian Dictionary as a threshold to the era of language technological applications."]}